THE URGENCY OF ENTREPRENEURSHIP EDUCATION IN SHAPING AN INDEPENDENT GENERATION - Rahmawati Alwi; Widya Fatmah; Zulkifli; Lailatul Khadaliyah; Khandika Syifa; Muhamad Awalurizal (PT. Jurnal Center Indonesia Publisher, 2026)
Entrepreneurship education is a strategic instrument in addressing global social and economic challenges, particularly those related to the low level of independence of the younger generation. The still-dominant orientation of graduates as job seekers demonstrates the need for a paradigm shift in education toward developing an independent, creative, and adaptive generation. This study aims to analyze the urgency of entrepreneurship education in developing an independent generation through a library approach. The research method used is library research, examining scientific journal articles, academic books, and educational policy documents published in the last five years (2021–2025). Data analysis was conducted using content analysis techniques to identify the concepts, values, and role of entrepreneurship education in developing an independent generation. The study results indicate that entrepreneurship education contributes significantly to fostering independence, creativity, responsibility, risk-taking, and problemsolving skills. Therefore, there is a high urgency for entrepreneurship education to be systematically integrated into the education system to develop an independent and competitive generation.